Study of Effect Changing the Blade Shape and Lift Angles on Horizontal Wind Turbine - Ichsan Astanto; Fatahul Arifin; Yohandri Bow; Sirajuddin (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
The lack of energy commodities such as coal and petroleum makes the cost of these commodities soar. This event shows how much countries in the world are still very dependent on fossil fuels, and it is fitting that the transition to new renewable energy can be realized soon, low emission and environmentally friendly energy is the hope in the future. Indonesia has a supply of renewable energy sources that are abundant is a great force for this clean energy revolution. The momentum of the presence of the first wind farm in Indonesia operating in Mattirotasi Village, Sidrap Regency, Central Sulawesi in Indonesia with a wind power plant capacity (PLTB) of 75 MW is positive evidence that the government is starting to pay more attention to the development of renewable energy technology in Indonesia. Turbine technology that is able to optimize wind speed in Indonesia must be the answer so that this energy is more useful. In this study, the idea for an experimental analysis of